Uncovering the Metabolic Footprint of New Psychoactive Substances by Metabolomics: A Systematic Review - Ana Sofia Almeida; Paula Guedes de Pinho; Fernando Remião; Carla Fernandes (Molecules)
New psychoactive substances (NPSs) emerged in the 2000s as legal alternatives to illicit drugs and quickly became a huge public health threat due to their easy accessibility online, limited information, and misleading labels. Synthetic cannabinoids and synthetic cathinones are the most reported groups of NPSs. Despite NPSs being widely studied, due to their structural diversity and the constant emergence of novel compounds with unknown properties, the development of new techniques is required to clarify their mode of action and evaluate their toxicological effects. Metabolomics has been a useful tool to evaluate the metabolic effects of several xenobiotics. Herein, a systematic review was performed, following PRISMA guidelines, regarding metabolomic studies on synthetic cathinones and synthetic cannabinoids to evaluate their effects in cellular metabolism. In the studies, in vivo models were the most employed (86%) and the analysis mostly followed untargeted approaches (75%) using LC-MS techniques (67%). Both groups of NPSs seem to primarily interfere with energy metabolism-related pathways. Even though this type of study is still limited, metabolomics holds great promise as a tool to clarify mechanisms of actions, identify biomarkers of exposure, and explain the toxicological effects of NPSs.